The origins of asthma - Sly, Peter (Henry Stewart Talks, 2011)
Asthma is a multifactorial condition, Asthma as a "Syndrome", Causes of asthma: genetic and environmental, Development of asthma, Growth of respiratory system, Maturation of the immune system, Prenatal exposures which cause asthma, Asthma risk factors, Considering atopy when assessing asthma risk